Regioselective Synthesis of β‐Aryl Enaminones and 1, 4, 5‐ Trisubstituted 1, 2, 3‐Triazoles from Chalcones and Benzyl Azides. Issue 16 (30th July 2014) - Xie, Yu‐Yang; Wang, Ying‐Chun; Qu, Hong‐En; Tan, Xian‐Chun; Wang, Heng‐Shan; Pan, Ying‐Ming
Abstract A highly regioselective synthesis of β‐aryl enaminones and 1, 4, 5‐trisubstituted 1, 2, 3‐triazoles from chalcones and benzyl azides based on reaction solvent selection is reported. In the presence of a catalytic amount of Ce(OTf)3, reactions of chalcones with benzyl azides in DMF at 100 °C afforded densely substituted Z‐β‐aryl enaminones in good to excellent yields, whereas treatment of chalcones with benzyl azides in toluene at 100 °C selectively produced 1, 4, 5‐trisubstituted 1, 2, 3‐triazoles in excellent yields. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>